Human resources development in the Caribbean : overcoming the unemployment problem - Downes, Andrew S. (2000)
Provides an overview of the unemployment situation in the region. Examines the extent, character and reasons for unemployment there. Outlines the HRD initiatives pursued by the governments of the region and assesses the impact of these initiatives on the unemployment problem. Makes some suggestions for overcoming the unemployment problem from an HRD perspective.